2018
DOI: 10.2147/dddt.s149727
|View full text |Cite
|
Sign up to set email alerts
|

Organic mononitrites of 1,2-propanediol act as an effective NO-releasing vasodilator in pulmonary hypertension and exhibit no cross-tolerance with nitroglycerin in anesthetized pigs

Abstract: PurposeClinically available intravenous (IV) nitric oxide (NO) donor drugs such as nitroglycerin (GTN) cause systemic hypotension and/or tolerance development. In a porcine model, novel NO donor compounds – the organic mononitrites of 1,2-propanediol (PDNO) – were compared to GTN with regard to pulmonary selectivity and tolerance development. The vasodilatory effects of inorganic nitrite were investigated.Materials and methodsIn anesthetized piglets, central hemodynamics were monitored. At normal pulmonary vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Despite cardiovascular effects of GTN and organic nitrates being well established for decades, the search for novel NO-donors for clinical use is still ongoing, and the study of the mechanisms involved in tolerance development continues [ 32 , 33 , 34 , 35 ]. In the search for new products available both as potential drugs and for use as probes to further examine the mode of action of organic nitrates, in a previous work we characterized compounds 1 – 3 for their in vitro NO-dependent vasodilating activity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite cardiovascular effects of GTN and organic nitrates being well established for decades, the search for novel NO-donors for clinical use is still ongoing, and the study of the mechanisms involved in tolerance development continues [ 32 , 33 , 34 , 35 ]. In the search for new products available both as potential drugs and for use as probes to further examine the mode of action of organic nitrates, in a previous work we characterized compounds 1 – 3 for their in vitro NO-dependent vasodilating activity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, organic nitrite NO-donors are associated with less tolerance development and have therefore been presented as an attractive alternative. Previously, we designed a novel NO-donor, comprising the organic mononitrites of 1,2-propanediol, nitrosooxypropanol (PDNO), and found that it was an effective vasodilator in some different models of acute pulmonary hypertension [7,[9][10][11], and that it ameliorated renal ischemia reperfusion injury [12]. A phase I study in humans is ongoing (Eura-daCT No.…”
Section: Introductionmentioning
confidence: 99%
“…As a cardiovascular signalling molecule, nitric oxide (NO) has been shown to positively affect both lung and kidney function after aortic cross clamping by having a mitigating effect on the systemic inflammatory response [ 7 , 8 ]. Organic nitrate NO-donors (e.g., nitroglycerin) have the drawback of tolerance development in both the systemic and the pulmonary circulation [ 9 ]. In contrast, organic nitrite NO-donors are associated with less tolerance development and have therefore been presented as an attractive alternative.…”
Section: Introductionmentioning
confidence: 99%
“…18 The two novel organic mononitrites, 2-hydroxy propyl nitrite and 2-hydroxy-1-methylethyl nitrite (henceforth referred to as PDNO, Supplementary Figure S1 for molecular structure) are of particular interest to investigate in experimental acute PE, because this composition exhibited increased vasodilator selectivity toward the pulmonary circulation compared to for example nitroglycerin. 18,22 In addition, the vasodilatory action of PDNO was devoid of cross tolerance with nitroglycerin in the systemic and pulmonary circulations, indicating bioactivation via another pathway. 22 We hypothesized that PDNO intravenously can counteract the pulmonary hypertension in acute experimental PE, without inducing systemic side effects or gas exchange disturbances, nor methemoglobinemia.…”
Section: Introductionmentioning
confidence: 99%
“…18,22 In addition, the vasodilatory action of PDNO was devoid of cross tolerance with nitroglycerin in the systemic and pulmonary circulations, indicating bioactivation via another pathway. 22 We hypothesized that PDNO intravenously can counteract the pulmonary hypertension in acute experimental PE, without inducing systemic side effects or gas exchange disturbances, nor methemoglobinemia. To distinguish the effects of the PDNO solution from inorganic nitrite and NO gas, we first performed in vivo dose-response experiments with measurement of FENO, pulmonary and systemic hemodynamics, methemoglobin and plasma nitrite both in naive animals and in animals with pharmacologically induced pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%